Representasi Nilai Islam dalam Film Tarung Sarung - Siti Nurhaliza Muhlis; Nurhakki Nurhakki; Muhammad Qadaruddin (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2022)
This study analyzes the meaning of the local Bugis culture of South Sulawesi, which is unique, by using the theory of representation and semiotics. The research refers to the Sigajang Laleng Lipa culture. The type of research used is qualitative research, with the semiotic approach of Charles William Morris. Researchers observed relevant documents and found local cultural representations and Islamic meanings in each scene. The study results show that every sign of several scenes has a meaning that is difficult for ordinary people to understand. Some scenes in the film do not follow the teachings, but some have Islamic values. Appropriate values must be maintained, but inappropriate values can be reduced to appropriate ones. This research will likely impact maintaining the da'wah model with a local cultural approach, which is mediated by local cultural films.